The Correlation between Mandibular Condyle Shape and Temporomandibular Joint Conditions in Adult Females - Dominica Dian Saraswati Sumantri; Rosalina Tjandrawinata; Joko Kusnoto (Journal of Indonesian Dental Association, 2020)
Introduction: Conditions of the temporomandibular joint (TMJ) are affected by changes in movement and load during the joint’s function, which can cause morphological changes in hard tissues, such as the condyle. Panoramic radiographs can provide an indication of changes in hard tissues in TMJ. Objectives: The aim of this study was to determine whether there was any correlation between mandibular condyle shapes as seen on panoramic radiographs and TMJ conditions in adult female participants. Methods: The participants of this study were 75 adult female patients who underwent a panoramic radiograph examination conducted at the Maranatha Dental Hospital Radiology Unit. The patients were clinically examined based on the Research Diagnostic Criteria for Clinical Temporomandibular Disorder (RDC/TMD) questionnaire and also their panoramic radiographs. The data from the patients were categorized into four groups according to the RDC/TMD: normal, muscle disorders, disc displacement, and other joint diseases. Next, the radiographs were analyzed by two observers to determine the condyle shapes. Condyle shapes were classified into four groups: ovoid, flat, erosion, and osteophyte. Result: This study showed that of 75 patients, the right TMJ was normal in 34 patients, 2 patients had muscle disorders, 24 demonstrated disc displacement, and 15 had other joint diseases. For the left side of the TMJ, 22 radiographs were normal, 2 revealed muscle disorders, 35 identified disc displacement, and 16 showed other joint diseases. There was a strong agreement between the two observers in determining the right (κ=0.681) and left condyle shapes (κ=0.652). All participants’ findings indicated that condyle shapes and TMJ conditions are highly correlated for both the right (η2=0.889) and left condyle (η2=0.762). Conclusion: This study concluded that mandibular condyle shapes seen on panoramic radiographs and TMJ conditions in adult female participants were highly correlated.